Duration of apical development phases and their coincidence with growth rate in oat grown at high latitudes - Peltonen-Sainio, Pirjo; Rajala, Ari (MTT, 2004)
The growth cycle of oat can be divided into different main phases. Duration of these are dependent on genotype and environment. In this study, apical development and growth of 20 oat cultivars and lines released since 1920 s were monitored in two years. Pre-anthesis developmental phases were split into seven sub-phases: vegetative, pre-fertile, pre-abortion, generative, fertile pre-abortion, fertile, and abortion. Coincidence of apical development with leaf and tiller appearance and growth was studied and association of duration of main developmental phases with yield components analysed. Cultivar differences in duration of pre-anthesis sub-phases were not attributable to year of release though some tendencies appeared when four oldest cultivars were compared with four latest ones. The most marked change was prolonged duration of generative phase at the expense of duration of grainfilling period in modern cultivars. This was not, however, due to marked differences in cumulated degree days for generative phase, but shorter postanthesis period. Even though generative phase was not much changed by plant breeding, relative durations of sub-phases were somewhat: e.g. preabortion and fertile pre-abortion phases tended to be slightly shorter in modern cultivars in both years. Regarding measured growth parameters, modern cultivars had slightly lower number of leaves and higher Cdd °C demand for maximum leaf number, but lower demand for maximum tiller number. No constant effect of year of cultivar release were found on phyllochron, maximum green leaf number and maximum tiller number. Tillers tended to reach their peak value earlier compared to maximum leaf number in modern cultivars when compared to old ones. Relative elongation rate of the apex, uppermost node and uppermost stipule correlated negatively with duration of many of the pre-anthesis sub-phases.
Keywords: Ka; kasvuvaihe; erilaistuminen; abortoituminen; kaura; kehitys; kasvu; kukinto; röyhy; lämpösumma; versominen; anthesis; apex; development phase; grain-filling; growth; leaf number; phyllochron; oat; tiller